Evolutions and Interaction of Weak Discontinuity, Characteristic Shock in Gravity Wave Model - Bira, B. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this article, we consider a system of hyperbolic PDEs governed by the gravity wave model. From the application of symmetry analysis, we derive the group invariant exact solution for the governing system of equations. Further, through the solution in hand; we study the evolutionary behavior of weak discontinuity as well as characteristic shock. Finally, in order to highlight the physical significance, the interaction of weak discontinuity and characteristic shock is presented graphically.